Ethnozoology of the ritual and magic of the To Bada Ethnic Group in the Lore Lindu Biosphere Reserve, Central Sulawesi, Indonesia - Eny Yuniati; SERAFINAH INDRIYANI; JATI BATORO; Y. PURWANTO (Society for Indonesian Biodiversity, 2020)
Abstract. Yuniati E, Indriyani S, Batoro J, Purwanto Y. 2020. Ethnozoology of the ritual and magic of the To Bada Ethnic Group in the Lore Lindu Biosphere Reserve, Central Sulawesi, Indonesia. Biodiversitas 21: 2645-2653. The To Bada are a traditional ethnic group or community that lives in the Bada valley in the Lore Lindu biosphere reserve. In some spheres, the Bada people still maintain traditional values and principles. This study aims to identify the animals used in rituals, magical and traditional activities among the Bada people, to investigate the ethnozoological perceptions and conceptions that are influenced by social and cultural factors, and to determine animal conservation status. The research method used was a participatory exploration survey with in-depth, open-ended, and semi-structured interviews. The results demonstrate that animal parts used in rituals and various traditions include eggs, heads, horns, blood, flesh, and the whole body. In addition, some body parts and product animals are believed to have magical value, such as fur, sound, and the whole body. The animals used most in rituals are the buffalo, cow, pig, free-range chicken, and partridge. Animals that have magical value are birds and mammals.